2017
DOI: 10.1177/0194599817690723
|View full text |Cite
|
Sign up to set email alerts
|

Current Interview Trail Metrics in the Otolaryngology Match

Abstract: Objectives To identify how applicants to otolaryngology residency determine how to apply to, interview with, and rank programs on the interview trail and to determine the extent of the financial burden of the otolaryngology interview trail. Study Design Web-based survey distributed in March and April 2016. Setting Otolaryngology residency applicants throughout the United States. Subjects and Methods Applicants to otolaryngology residency during the 2016 match cycle and current otolaryngology residents were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 10 publications
2
42
1
Order By: Relevance
“…Furthermore, applying to residency is expensive. Cabrera‐Muffly et al reported that the average OHNS applicant spent $5,400 on application fees and interview travel expenses . Chang and Erhardt estimated that the aggregate OHNS application cost was approximately $560,395 in 2015 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, applying to residency is expensive. Cabrera‐Muffly et al reported that the average OHNS applicant spent $5,400 on application fees and interview travel expenses . Chang and Erhardt estimated that the aggregate OHNS application cost was approximately $560,395 in 2015 .…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the NRMP applicant survey, which showed that in 2017 matched applicants received 19 interview offers but were only able to attend and rank 14 . Furthermore, according to Cabrera‐Muffly et al, 74% of applicants reported declining an interview offer due to scheduling conflicts . In comparison, fields such as diagnostic radiology tend to offer a wider selection of interview dates, and thus conflicts may play a role in mitigating hoarding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application fees for the SF Match Residency Matching Services were used to determine the mean application cost for matched and unmatched applicants. 16 Existing literature was used to estimate the applicant cost per interview 3,[6][7][8][9][10][11][12][13][14][15] ; the mean of these reports was used.…”
Section: Methodsmentioning
confidence: 99%